The Organism - Baedke, Jan (Cambridge University Press, 2026)
This Element discusses long-standing challenges to base biological reasoning and practice on the concept of organism. Currently, after many decades dominated by the paradigm of the gene, the organism is making a comeback in the bio- and biomedical sciences. This title is also available as Open Access on Cambridge Core.